Mapping research trends in information infrastructure: a bibliometric review of computer science and ICT (2013–2023) - Zulazeze Sahri,; Norjansalika Janom, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study presents a comprehensive bibliometric analysis of research trends in information infrastructure (Infostructure) within the Computer Science and Information and Communication Technology (ICT) domains, covering publications from 2013 to 2023. Utilising the Scopus database, 1179 articles were systematically analysed through keyword searches, using VOSViewer for mapping publication trends, keyword co-occurrence, and citation analysis. The findings reveal key research clusters, including network and communication technologies, data management, security and privacy, and digital transformation, with China, Russia and the United States leading in contributions. A notable increase in publications was observed from 2020 onwards, signaling a growing interest in Infostructure’s role in digital transformation. While the study focused on English language articles, future research should consider expanding to broader datasets and interdisciplinary perspectives. This research provides a valuable foundation for understanding Infostructure’s evolution over the past decade. It offers insights for future studies supporting emerging technologies such as IoT, AI, and blockchain.